Influence of quercetin on haematological indices and biomarkers of oxidative stress in the serum of rats exposed to atrazine (2010)
The study was carried out to compare thè effects of quercetin (QT) at doses of 5mg/kg (QQ and lOmg/kg (Q|0) against thè hematological toxicity and oxidative stress caused by atrazine (ATR). Male rats were oraily gavaged with ATR at a dose of 120mg/kg for 16 days. Erythropenia, leucopenia was observed in ATR treated rats. Other hematological variables such as packed celi volume (PCV), hemoglobin concentration (HGB), mean celi hemoglobin concentration (MCHC), mean corpuscular volume (MCV), neulrophils (NEU), lymphocytes (LYM) and blood platelet (PLT) showed no significant change with respect to thè control values. The activities of thè antioxidant defense molecules including superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), glutathione-S-transferase (GST) and glutathione (GSH) were decreased; malondialdehyde (MDA) level increased but catalase (CAT) activity showed no change.Co-administration of Q5 did not prevent thè oxidative stress and thè fiematological alterations caused by ATR. In these groups of animals, thè values of PLT and NEUT were increased while LYM decreased indicating more pronounce hematological changes. The changes in both thè biochemical and hematological variables were noi malized to thè control values on co-administration of Ql0. We suggest that thè antioxidant activities of QT al a doses of lOmg/kg could be responsible for its protecti ve effects against ATR-induced oxidative stress and hematological toxicity.